The SKAl-Low Telescope: The Station Design and Prototyping - De Vaate, J.; Bast, J.; Benthem, P.; Gerbers, M.; Wijnholds, S.; Booler, T.; Colgate, T.; Crosse, B.; Emrich, David; Hall, Peter; Juswardy, Budi; Kenney, David; et al. (2018)
© 2018 International Union of Radio Science URSI. The Square Kilometre Array (SKA) [1] telescope consists in its first phase of two arrays, a dish array to be constructed in South Africa and a low frequency aperture array to be constructed in Western Australia. The aperture array, SKAI-Low, will consist of 512 stations, each with 256 wide bandwidth log periodic antennas. The frequency range of SKAI-Low is 50 to 350 MHz. The Low Frequency Aperture Array (LFAA) consortium is tasked to design the station, the infrastructure around them and the station signal processing.